2010
DOI: 10.1029/2009ja014848
|View full text |Cite
|
Sign up to set email alerts
|

A study of solar energetic particle events of 1997–2006: Their composition and associations

Abstract: [1] We examined the properties and associations of 280 solar proton events that extended above 25 MeV and occurred in the years 1997-2006. The properties include early peak intensities of five species over several energy ranges and the intensity-time profiles. Solar event associations were made for as many events as possible. The solar parameters determined include coronal mass ejection and flare properties and radio emissions from a wavelength range of meters to kilometers. The events were divided into five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
225
2
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(241 citation statements)
references
References 33 publications
(51 reference statements)
10
225
2
4
Order By: Relevance
“…The event selection is based on two previously published works, the comprehensive SEP catalog given by Cane, Richardson, and von Rosenvinge (2010) and a few events that were added from Klein et al (2011). We selected SEP events associated with flares with peak soft X-ray (SXR) flux 9×10 −6 W s −2 (GOES class C9) which were located on the solar disk including limb events (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The event selection is based on two previously published works, the comprehensive SEP catalog given by Cane, Richardson, and von Rosenvinge (2010) and a few events that were added from Klein et al (2011). We selected SEP events associated with flares with peak soft X-ray (SXR) flux 9×10 −6 W s −2 (GOES class C9) which were located on the solar disk including limb events (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The association rate is slightly lower for the western ICME/vicinity SEP events (83 %) than for the eastern ones. The reliability of the association rates calculated here depends on the correct SEP-parent activity identification adopted from Cane, Richardson, and von Rosenvinge (2010). During the detailed analysis of the eastern events however, we found that for three No-association cases the parent flare/CME might be a later event pair that is associated with an EIT disturbance.…”
Section: Sep Events and Eit Waves During Solar Cycle 23: Overall Assomentioning
confidence: 99%
See 3 more Smart Citations